The role of mineralogical and textural complexity in the damage evolution of brittle rocks - Özge Dinç Göğüş; Elif Avşar; Kayhan Develi; Ayten Çalık (Scientific Reports)
Abstract In brittle rocks, deformation is characterized by the initiation and propagation of cracks at both microscale and mesoscale levels. This study explores how rock texture influences the evolution of cracking networks and progressive rock damage results under uniaxial compression. 3D discrete analyses were employed to identify the critical stresses of three different rock types. Thin sections were prepared from uniaxially loaded core samples at these stresses and crack patterns were captured under a polarizing microscope. The fractal box dimension method was used to quantitatively analyze the crack patterns for each rock type at each stress level. The novelty of this research is revealing the relationship between the development of microcrack patterns and textural properties such as mineral orientation/distribution, interlocking, crystal cleavage/hardness, and the groundmass. Results show that the cracking tendency varies with rock type at each critical stress level. Specifically, diabase exhibited the highest crack intensity, attributed to the interlocking of hard plagioclase and pyroxene crystals. Furthermore, the cleavages in pyroxenes make diabase particularly susceptible to cracking, especially when they are oriented parallel or semi-parallel to the applied load. These findings highlight that rock texture is a crucial factor influencing microcrack development, which should be considered in rock engineering applications.